Hubungan Pola Asuh Orang Tua dengan Kesiapan Toilet Training Pada Anak Usia Toddler - Mail, Aidatul Fitri; Romdzati, Romdzati (Universitas Muhammadiyah Semarang, 2018)
The Relationship of Parenting Patterns with Toilet Training Readiness in Toddler Age ChildrenBackground: One of the child development tasks at toddler age is toilet training. Toilet training is a process of teaching children to control urination and defecation correctly and regularly. The readiness of toilet training in toddler age children is not only influenced by physical, psychological, mental, and parental readiness but can also be influenced by parenting patterns applied to children. There are three kinds of parenting styles including authoritarian, permissive, and democratic.Objective: This study aims to determine the relationship between parenting patterns and toilet training readiness for toddlers in Yogyakarta.Methods: This study is a non-experimental study with a correlational design through a cross-sectional approach. The sample in this study were 44 respondents with sampling through purposive sampling technique. Statistical test using chi-square with a=0.05.Results: This study shows that most parents apply democratic parenting, as many as 30 respondents (68.2%) with toilet training readiness as many as 22 respondents (73.3%). Correlation using chi-square test results obtained p value = 0.040.Conclusion: Based on data analysis, a significant value of p = 0.040 <0.05 was obtained, which means that there is a relationship between parenting patterns and toilet training readiness in toddler age children.Latar Belakang: Salah satu tugas perkembangan anak pada usia toddler adalah toilet training. Toilet training adalah suatu proses pengajaran kepada anak untuk mengontrol buang air kecil dan buang air besar secara benar dan teratur. Kesiapan toilet training pada anak usia toddler tidak hanya dipengaruhi oleh kesiapan fisik, psikologis, mental, dan orang tua tetapi bisa juga dipengaruhi oleh pola asuh orang tua yang diterapkan ke anak. Pola asuh orang tua ada tiga macam diantaranya otoriter, permisif, dan demokratis.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan pola asuh orang tua dengan kesiapan toilet training pada anak usia toddler Yogyakarta.Metode: Penelitian ini merupakan penelitian non-eksperimen dengan desain correlational melalui pendekatan cross-sectional. Sampel dalam penelitian ini sebanyak 44 responden dengan pengambilan sampel melalui teknik purposive sampling. Uji statistic menggunakan chi-square dengan a=0,05.Hasil: Penelitian ini menunjukkan sebagian besar orang tua menerapkan pola asuh demokratis yaitu sebanyak 30 responden (68,2%) dengan kesiapan toilet training sebanyak 22 responden (73,3%). Korelasi menggunakan uji chi-square didapatkan hasil nilai p=0,040.Kesimpulan: Berdasarkan analisis data diperoleh nilai signifikan p=0,040 < 0,05 yang berarti ada hubungan pola asuh orang tua dengan kesiapan toilet training pada anak usia toddler.